Nusûs Kitâb Ta'lîm Al-Lughah Al-'Arabiyyah Lil-Fasl As-Sâdis Al-Ibtidâ'i Biwazârati Ash-Shu'ûn Ad-Dîniyyah Al-Indûnîsiyyah 'Âm 2020 (Ad-Dars Al-Awwal Hattâ Ad-Dars Ath-Tsâlits Namûdzajan) - Mufarokah, Siti; Fajrina, Ilma Anas; Aziz, Abdul (Al-Uslub: Journal of Arabic Linguistic and Literature, 2024)
One of the reasons why students do not want to study Arabic is their difficulty in understanding Arabic texts. This study aims to know the quality of the texts in the Arabic language teaching book of the Ministry of Religious Affairs for the sixth grade of primary school in terms of educational, psychological, cultural and linguistic aspects in order to know the validity of the linguistic, spelling and syntax rules in the Arabic texts in this book. This study follows the descriptive approach, so this study begins with the process of reading, analyzing, then criticizing, and drawing conclusions. This study is a desk study. The study proved that the Arabic texts in the Arabic Language Teaching Book for the sixth grade of the Ministry of Religious Affairs in general are of good quality and valid from the educational, psychological and cultural point of view for Indonesians. This result is available after reading and analyzing the book by the researchers. However, in terms of the culture of the book, it combined the culture of Indonesian and Arabic, and this is good and does not detract from the quality of the texts of the book. As for the linguistic aspect, the movements and the writing of points are not written in some words, as well as some non-Arabic structures. Grammar rules in the book are not a problem. In conclusion, this book has a good general quality in terms of language, with a few errors in some situations. Keywords: Texts, education book, religious affairs